Reviews of new publications - Lambert, Frank (KUKILA, 2011)
del Hoyo, J, Elliot, A and Christie, D.A (eds) 2009. Handbook of the Birds of the World. Volume 14: 2009. Bush-shrikes to Old World Sparrows. Lynx Edicions, Barcelona del Hoyo, J, Elliot, A and Christie, D.A (eds) 2010. Handbook of the Birds of the World. Volume 15: 2010. Weavers to New World Warblers. Lynx Edicions, Barcelona